RESTORATION OF THE LEGAL STATUS OF LAND CERTIFICATES DUE TO THE PPAT'S NEGLIGENCE IN APPLYING THE PRINCIPLE OF PRUDENCE - Maulia Sakinah; Jamal Wiwoho; Adriana Grahani Firdausy (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the mechanism for restoring the legal status of land certificates that are legally flawed due to the negligence of Land Deed Officials (PPAT) in applying the principle of prudence in carrying out their duties. The urgency of this research is based on the increasing number of land disputes triggered by the lack of careful verification by PPATs, resulting in legally flawed deeds and certificates. This study uses a normative legal method by applying a statute approach and a case approach, focusing on an analysis of the Tangerang District Court Decision Number 1401/Pdt.G/2021/PN Tng as the object of study that has obtained permanent legal force. The results show that the PPAT's negligence in verifying the identity of the parties and the authenticity of the documents resulted in the creation of fictitious Sale and Purchase Deeds (AJB), which have implications for the unlawful transfer of rights. This negligence not only affects the validity of the deed but also invalidates the legal status of land certificates issued based on the legally flawed deed. The process of restoring the legal status of land certificates is carried out through the implementation of court decisions that have permanent legal force, accompanied by administrative steps by the National Land Agency (BPN) in accordance with the provisions of Government Regulation Number 24 of 1997 concerning Land Registration and Regulation of the Minister of ATR/BPN Number 21 of 2020 concerning Handling and Settlement of Land Cases. The novelty of this research lies in the in-depth analysis of the synergy between judicial and administrative authorities in the process of restoring the legal status of land certificates damaged due to negligence of PPAT. This research emphasizes the urgency of implementing the principle of prudence by PPAT as an important instrument in ensuring legal certainty and preventing the emergence of land disputes in the future.